Skeptisisme profesional auditor pada kantor akuntan publik di Sumatera - Zainal Abidin Zein; Yuneita Anisma; Christina ' (Jurnal Ekonomi, 2010)
This article analyzed influence some variable on professional skepticism attitude of auditor at PublicAccountant Firm in Sumatra region. Data collected from respondent auditor used questioner by mail.There are 165 questioners send to auditors, but 96 questioners resend and only 90 questioners are valid.The study uses multiple regression linear method as tools analysis. Result this study only cangeneralized auditor opinions which working at Public Accountant Firm in Sumatra region. Experience,ethics awareness, audit situation, and professionalism variables influence on skepticism attitude ofauditor, and variable audit situation as dominant variable.